EFEKTIVITAS KOMUNIKASI ORGANISASI DALAM MANAJEMEN PROGRAM KERJA POS YANDU - Fajriyah, Nur; Ri’aeni, Ida; Yusron, Ahmad (School of Communication - Atma Jaya Catholic University of Indonesia, 2019)
Authors must supply a structured abstract in their submission, which includes; Purpose, Design/methods/approach, Findings/results, Conclusions. Between 100 -maximum 200 words in total excluding keywords. The abstract is in two languages, English and Indonesian. English abstract first, when the main content is in In Komunikasi menjadi hal yang sangat penting dalam berorganisasi. Komunikasi dalam suatu organisasi dibutuhkan dalam mempelajari, memperbaiki, serta membangun kemajuan organisasi. Metode yang digunakan dalam penelitian ini adalah metode pendekatan deskriptif kuantitatif. Peneliti menggunakan lima indikator dalam mengukur efektivitas komunikasi organisasi di Posyandu Desa Keraton. Diantaranya adalah pemahaman, pengaruh sikap, tindakan, keterbukaan dan kesetaraan. Berdasarkan hasil penelitian, kelima indikator efektivitas komunikasi organisasi dalam penelitian ini memiliki masing-masing skor atau nilai. Pada intinya kesetaraan kontribusinya kecil terhadap efektivitas komunikasi dalam organisasi yang dijalankan posyandu.—— Communication becomes very important in the organization. Communication within an organization needed to learn, improve, and build the organization's progress. The method used in this research is quantitative descriptive approach. We uses five indicators to measure the effectiveness of organizational communication in Posyandu (IHC) in Keraton, Suraneggala, Cirebon. Among them is the understanding, influence attitudes, actions, openness and equality. Based on the results of the study, the five indicators of effectiveness of organizational communication in this study have respective scores or grades. In principal, equality provides a small contribution to the effectiveness of communication in organizations that are run in posyandu.